Different methods of synthesizing poly(glycerol sebacate) (PGS): A review - Godinho, Bruno; Gama, Nuno; Ferreira, Artur (Frontiers in Bioengineering and Biotechnology, 2022)
The poly (glycerol sebacate) (PGS) is a biodegradable elastomer that has been gaining attention as a potential material for biological tissue engineering applications. The conventional method of synthesis, firstly presented in 2002, is based on the polycondensation of glycerol and sebacic acid, but it is a time-energy consuming process. Over the last years, new approaches for obtaining PGS, PGS blends and PGS copolymers have been attempted, not only with the aim of reducing the time and energy required to obtain a final material, but also to adjust the properties and processability of the PGS-based materials to the desired applications. This review compiles more than 20 years of PGS synthesis comprehension, reported inconsistencies, and proposed alternatives to obtain PGS polymer structure or PGS derivatives in a faster way and with tailor-made properties. Synthesis conditions like temperature, time of reaction, reagents ratio, atmosphere, catalysts, microwave assisted synthesis and PGS modifications (urethane and acrylate groups, blends, and copolymers) were revisited to present and discuss the diverse alternatives to produce and adapt PGS.